L'effet de la correction assistée par ordinateur (CAO) sur la construction des compétences orthographiques des apprenants de FLE en Algérie - Abdelmalek Talbi; Denis Legros (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication, 2018)
The spelling difficulties of FFL (French as a Foreign Language) learners in Algeria are mainly due to the non-biunivocal phonographic correspondences of French spelling. Research shows that correctors facilitate the detection of errors but that they don't contribute to the construction of transferable orthographic knowledge. The aim of this research is to analyze the effects of a new generation corrector, the corrector Robert, on the development of students spelling skills in terms of phonogram errors. A sample of twenty students of 1st year French license was subjected to four tasks: dictation 1 (pre-test evaluation), 1st correction (spelling review with corrector), 2nd correction (spelling review without corrector) and dictation 2 (post-test evaluation). Our results show that the guided and oriented use of a corrector supports the correction of phonogram errors and improves the transfer of spelling skills.